(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, we explore innovative pedagogical technologies as modern methods and means of teaching in the education system. It is shown that innovative pedagogical technologies not only create the basis for the competitiveness of any institution in the educational services market, but also make it possible to intensively develop the personality of a teacher and a student, democratize the interaction and communication of a teacher and a student, humanize the educational process, focus students on active learning and self-education, professionalism of teachers. and so on.